2019
DOI: 10.7149/opa.52.1.51015
|View full text |Cite
|
Sign up to set email alerts
|

Proposal to calculate the circadian component in lighting projects

Abstract: There are international norms which define methods for characterizing indoor luminaries in terms of photopic considerations and visual requirements, but lighting impacts in humans in others ways than those. Light in buildings is part of the environment, the discovery of the ipRGC cells in the human retina, and its associated action spectra, lead to the introduction of initial concepts such as circadian action functions and circadian action factors. An innovative methodology is proposed and evaluated to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Illuminations, both horizontal and vertical, critically depend on the dimensions of the room and the reflectance of its walls and furniture [23,34,35]. Room surface reflectance is an important factor in achieving a high illuminance and has even been described as being much more important than the light that arrives through the windows, particularly in the winter months and depending on the orientation of and the distance from the windows to the workstation [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illuminations, both horizontal and vertical, critically depend on the dimensions of the room and the reflectance of its walls and furniture [23,34,35]. Room surface reflectance is an important factor in achieving a high illuminance and has even been described as being much more important than the light that arrives through the windows, particularly in the winter months and depending on the orientation of and the distance from the windows to the workstation [34].…”
Section: Discussionmentioning
confidence: 99%
“…The CCT, CRI, Fidelity Index (Rf), Relative Gamut Index (Rg), Local Chroma Shift (Rcs,hj(%)), and Local Color Fidelity (Rf,hj) are parameters used to quantify different objective aspects of color rendition, including average color fidelity and gamut area, as well as 16 values (j from 1 to 16) each for hue-specific chroma shift, hue shift, and color fidelity in lighting devices [20,21]. Recently, several measuring experimental setups have been described for standardizing lighting experiments given the variability in the lighting results [22][23][24]; in addition, scholars have discussed the complexity of lighting design, described potential effects that should be considered by researchers [25], and reported the physiological and seasonal changes that can occur [10,26]. To improve both visual and nonvisual effects in lighting projects, it seems that SPD optimization is required.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those of this study since our CCT measurements vary between 4892 and 12,380 K. However, due to the low correlation between the CCT and circadian effects, it is considered that the CCT is not a good indicator to establish the levels of circadian response [20,37]. Although Rea et al reported that LEDs with high CCTs above 5299 k could slightly stimulate the circadian system after one hour of exposure to outdoor lighting at 95 lux, when taking advantage of natural light in interior spaces, the reflectance of the walls must also be considered because they vary the CCT and the spectral composition of light that regulate the circadian system [38][39][40]. Additionally, our measurements show that for indoor purposes where daylight reaching outdoors is important, new parameters, such as the seasonality, façade orientation and altitude of the sun, are substantial and have sufficient contributions that should always be considered.…”
Section: Circadian Characteristicsmentioning
confidence: 99%